Structural basis of the phosphorylation-independent recognition of cyclin D1 by the SCF(FBXO31) ubiquitin ligase - Li, Yunfeng (Proc Natl Acad Sci U S A, 2018)
Ubiquitin-dependent proteolysis of cyclin D1 is associated with normal and tumor cell proliferation and survival. The SCF(FBXO31) (Skp1–Cul1–Rbx1–FBXO31) ubiquitin ligase complex mediates genotoxic stress-induced cyclin D1 degradation. Previous studies have suggested that cyclin D1 levels are maintained at steady state by phosphorylation-dependent nuclear export and subsequent proteolysis in the cytoplasm. Here we present the crystal structures of the Skp1–FBXO31 complex alone and bound to a phosphorylated cyclin D1 C-terminal peptide. FBXO31 possesses a unique substrate-binding domain consisting of two β-barrel motifs, whereas cyclin D1 binds to FBXO31 by tucking its free C-terminal carboxylate tail into an open cavity of the C-terminal FBXO31 β-barrel. Biophysical and functional studies demonstrate that SCF(FBXO31) is capable of recruiting and ubiquitinating cyclin D1 in a phosphorylation-independent manner. Our findings provide a conceptual framework for understanding the substrate specificity of the F-box protein FBXO31 and the mechanism of FBXO31-regulated cyclin D1 protein turnover.